Indicators of the Intestinal Microflora of Laboratory Animals (Rats, Rabbits and Guinea Pigs) With Dysbacteriosis in the Dynamics of Age - D.I., Abdukarimov; K.L., Shagulyamova; N.A., Mirzaakhmedova; K.M., Turdaliev; L.A., Shigakova (RA Journal of Applied Research, 2022)
Dysbiotic disturbances in the qualitative and quantitative composition of the microflora of the body and its functions, caused by various reasons, still remain one of the leading and most difficult problems to solve in modern medicine. In experimental modeling of dysbiosis in laboratory animals, increased adhesion of opportunistic microorganisms to intestinal epithelial cells was revealed. The mechanisms of development of dysbacteriosis and its consequences are very complex and multifaceted, so the need to find tools that can cover as many links of this pathogenesis as possible is still relevant for medicine.